Storytelling in Experience Creation: Case Kaisus Lappland - Alapuranen, Pipsa (Lapin ammattikorkeakoulu, 2015)
The experience dominant logic has been transforming the tourism industry drastically and the tourism companies need to develop new ways to create deeper and more meaningful experiences for the tourists. Stories are one of the key elements in the creation of memorable experiences and therefore this thesis focuses on the role of storytelling in holistic and continuing tourism experience creation process. The research questions were set as “What stories and storytelling are in tourism context?”, “How storytelling is used in meaningful experience creation?” and “How can it be used in ‘case Kaisus Lappland’?”. The theoretical background information was gained through literature material, and the indepth interviews focused on gaining real life examples regarding the thesis topic. The research findings showed the diversity of stories and storytelling in holistic experience creation. The efficience and importance of this tool was recognized, and its role for creating meaningful tourist experiences was discovered. The aim of the thesis was to adapt the gained knowledge for future experience product development for the commissioner. This was conducted by providing three practical improvement suggestions which focused on enhancing the already existing products by deepening and emphasizing the role of authentic stories in dramatization of holistic and continuous experience creation. Matkailualan keskittyessä yhä enemmän elämyksiin yritysten on muutettava toimintaansa ja kehitettävä innovatiivisia toimintatapoja merkittävien ja mieleenpainuvien elämysten tuottamiseksi. Tarinoiden ollessa keskeisessä roolissa edellämainitunlaisten kokemusten tuottamisessa, ovat ne tämän opinnäytetyön painopisteenä käsiteltäessa kokonaisvaltaista ja jatkuvaa matkailun elämystuontantoprosessia. Opinnäytetyön tutkimuskysymykset ovat: Mitä tarinat ja tarinankerronta ovat matkailussa?, Kuinka tarinankerrontaa käytetään osana merkittävän elämyksen luontia?, sekä Kuinka tarinankerrontaa voidaan käyttää osana 'case Kaisus Lapplandissa'?. ...